2007
DOI: 10.1104/pp.106.092254
|View full text |Cite
|
Sign up to set email alerts
|

DELLAs Contribute to Plant Photomorphogenesis

Abstract: Plant morphogenesis is profoundly influenced by light (a phenomenon known as photomorphogenesis). For example, light inhibits seedling hypocotyl growth via activation of phytochromes and additional photoreceptors. Subsequently, information is transmitted through photoreceptor-linked signal transduction pathways and used (via previously unknown mechanisms) to control hypocotyl growth. Here we show that light inhibition of Arabidopsis (Arabidopsis thaliana) hypocotyl growth is in part dependent on the DELLAs (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
223
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(239 citation statements)
references
References 62 publications
9
223
3
4
Order By: Relevance
“…61), whereas both gibberellins and brassinosteroids have been shown to be involved in dark-light transition and photomorphogenesis (i.e., influence of light on plant morphogenesis), demonstrated for hypocotyl growth and elongation. 62,63 With respect to nutrient response, auxin, cytokinin, ethylene, gibberellins and abscisic acid have been shown to affect root and shoot development in response to nutrient conditions; conversely, mineral nutrient conditions have been shown to influence hormone biosynthesis, transport and signaling (reviewed in ref. 20, 24 and 64).…”
Section: Other Phytohormones and Plant Responses To Environmental Cuesmentioning
confidence: 99%
“…61), whereas both gibberellins and brassinosteroids have been shown to be involved in dark-light transition and photomorphogenesis (i.e., influence of light on plant morphogenesis), demonstrated for hypocotyl growth and elongation. 62,63 With respect to nutrient response, auxin, cytokinin, ethylene, gibberellins and abscisic acid have been shown to affect root and shoot development in response to nutrient conditions; conversely, mineral nutrient conditions have been shown to influence hormone biosynthesis, transport and signaling (reviewed in ref. 20, 24 and 64).…”
Section: Other Phytohormones and Plant Responses To Environmental Cuesmentioning
confidence: 99%
“…Gibberellins (GAs) exert an opposite effect to light on photomorphogenesis 2 . GAs promote etiolated growth, whereas GA-deficiency induces a partially de-etiolated phenotype in the dark, which is reverted by a lack of DELLA function 2,9 . DELLAs function as key repressors of GA-responsive growth, by inhibiting GA-regulated gene expression 5 .…”
mentioning
confidence: 99%
“…For this, we took advantage of the TRANSPLANTA (TPT) collection of Arabidopsis lines for conditional TF overexpression under the regulation of a b-estradiol-inducible promoter (Coego et al, 2014). It has been reported that GAs promote skotomorphogenesis, such that etiolated seedlings growing under GA-limiting conditions display photomorphogenic traits, such as short hypocotyls, an open apical hook, and unfolded cotyledons (Alabadí et al, 2004(Alabadí et al, , 2008Achard et al, 2007b;Gallego-Bartolomé et al, 2011). We screened 641 TPT lines representing 276 TFs growing in darkness under two different conditions: 10 nM GA biosynthesis inhibitor paclobutrazol (PAC) with 5 mM b-estradiol for 3 d to score their apical hook angle and 1 mM PAC with 5 mM b-estradiol for 7 d to score the angle between cotyledons.…”
Section: Identified Della Interactors Affect Ga Responsesmentioning
confidence: 99%
“…The GA metabolic pathway is responsive to environmental factors both biotic and abiotic (Achard et al, 2006(Achard et al, , 2007a(Achard et al, , 2007bZhao et al, 2007;Alabadí et al, 2008;Navarro et al, 2008;Stavang et al, 2009). Moreover, the GA pathway is also modulated by endogenous factors, such as the circadian clock , as well as other hormones, including auxins, ethylene, or cytokinins (Jasinski et al, 2005;Frigerio et al, 2006;Achard et al, 2007a).…”
mentioning
confidence: 99%